2017
DOI: 10.1093/eurpub/ckw249
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of barriers to active commuting to school in Spanish children and adolescents

Abstract: : Understanding parental barriers is crucial to promote active commuting to school since the parental perceptions influence how young people commute. This study examined parental barriers to active commuting to school among Spanish children and adolescents, and their association with their gender and the usual mode of commuting. Parents of children ( n = 628) and parents of adolescents ( n = 151) from Granada (Spain) completed a paper-based questionnaire about perceived parental barriers to active commuting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
2
44
2
2
Order By: Relevance
“…It seems that children active travels to/from school were influenced by other environmental factors such as traffic safety, among others, which may move them away from more direct routes (i.e., usually with high levels of traffic, air pollution and noise). This influence is in line with other previous studies (e.g., [17][18][19]63]). In addition, the recent study of Egli et al (2019) [70] found that children who actively travel to school are aware of traffic safety, air pollution and prefer commuting with friends and/or family members to socialize.…”
Section: School-built Environment and Home-school Route Correlates Ofsupporting
confidence: 93%
See 3 more Smart Citations
“…It seems that children active travels to/from school were influenced by other environmental factors such as traffic safety, among others, which may move them away from more direct routes (i.e., usually with high levels of traffic, air pollution and noise). This influence is in line with other previous studies (e.g., [17][18][19]63]). In addition, the recent study of Egli et al (2019) [70] found that children who actively travel to school are aware of traffic safety, air pollution and prefer commuting with friends and/or family members to socialize.…”
Section: School-built Environment and Home-school Route Correlates Ofsupporting
confidence: 93%
“…Considering these factors, observed rates of ACS were higher in children than in adolescents [14], and in those of lower versus (vs.) higher socio-economic status [15,16]. Likewise, among others, parental concerns regarding personal and traffic safety [17,18], as well as safety perceptions of walking routes [19] also influence how young people travel to/from school.…”
Section: Acs Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey participants reported family members as important motivators for learning to drive behaviours and attitudes. Previous research has shown that parents are 'critical gatekeepers' in the mobility decisions for children and adolescents (Kerr et al 2006;Lorenc et al 2008), particularly relating to active transport to school decisions (Hopkins and Mandic 2017;Huertas Delgado et al 2017;Aibar et al 2018), and learn to drive behaviours (Hopkins 2016). As such, mobility practices of adolescents need to be understood in the context of family pressures, relationships and interactions.…”
Section: Discussionmentioning
confidence: 99%